Genetic Variation Of The Japanese Quail (Coturnix Coturnix Japonica) Based On Biochemical Polymorphism (2017)
The study aimed at characterizing the Japanese quail using biochemical markers. Blood protein polymorphism of one hundred and sixty-six (166) Japanese quails of both sexes comprising of 83 each of mottled brown and white quails were analysed using cellulose acetate paper electrophoresis. Six loci which includes hemoglobin (Hb), transferrin (Tf), albumin (Alb), carbonic anhydrase (CA), alkaline phosphatase (Alp) and esterase-1 (Es-1) were tested. All the loci tested were polymorphic with each locus having two co-dominant alleles controlling three genotypes. Allele B was predominant at Hb, Tf and Es-1 locus with frequencies 0.90, 0.55, and 0.77, respectively while Allele A was predominant at Alb and Alp locus with frequencies 0.83 and 0.58 respectively. The Allele A had generally lower frequencies than B at the CA loci having values of 0.43 - Brown, 0.38 - White and 0.40 – overall. The mean observed heterozygosity (Hₒ) was 0.48 with brown and white quails having Ho values of 0.47 and 0.49 respectively, and the expected heterozygosity was observed to be higher in white quails (0.39) than in the mottled brown (0.31). The genetic distance (0.0534) between white and brown quails in this study showed little genetic differentiation between the brown and the white quails. Dendogram generated from the genetic distance values indicated that the two strains had common origin.